The Effectiveness of Cuscuta sp. Crude Extract as an Antibacterial of Streptococcus agalactiae in Tilapia Fry Oreochromis niloticus - Fidyandini, Hilma Putri; Setyawan, Agus; Noor, Huriyatul Fitriyah; Sakti, Doni Bilga Komara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Tilapia (Oreochromis niloticus) is a leading freshwater fishery commodity in Indonesia. However, aquaculture has an obstacle, namely the lack of healthy fish seeds due to Streptococcus disease caused by the bacteria Streptococcus agalactiae. One natural ingredient that is known to have antibacterial properties is dodder (Cuscuta sp.). At the Fisheries Cultivation Laboratory at the University of Lampung, the aim of the research was to determine the efficacy of dodder extract in controlling bacterial infections caused by S. agalactiae in tilapia fry. CE was attempted on an in vitro scale against the microorganism S. agalactiae using a circle dispersion strategy. Then, CE on the dodder was tried for Least Inhibitory Focus (MIC) with a convergence of 100 ppm, 300 ppm, 500 ppm and 700 ppm. Poisoning test on tilapia seeds with focus referring to the MIC test. The research results revealed that the yield of tali putri extract was 1146 percent. Steroids, flavonoids, alkaloids, saponins and tannins are the components of the active compound content of dodder extract in phytochemical tests. The results of the separate GC-MS dodder test produced the compound 9-octadecenoate with a maintenance area of 10.38%. Dodder removal can withstand S. agalactiae from a concentration of 100 ppm with an inhibition zone of 6.64 mm to thickness without weakening with an inhibition zone of 7.50 mm. The MIC test results show that 100 ppm is the optimal concentration for wound healing. The results of the damage test (LC50) at a concentration of 100 ppm showed that the death rate of tilapia fry was the smallest compared to other fixations. It is possible that CE dodder can be made as an antibacterial against S. agalactiae.